2017
DOI: 10.1002/jssc.201700695
|View full text |Cite
|
Sign up to set email alerts
|

Advanced online mass spectrometry detection of proteins separated by capillary isoelectric focusing after sequential injection

Abstract: Capillary isoelectric focusing hyphenated with mass spectrometry detection, following the sequential injection of the carrier ampholytes and the sample zone, is highly efficient for the characterization of proteins. The main advantage of the sequential injection protocol is that ampholytes, with pH ranges, which are not supposed to cover the isoelectric points of the sample components, can be used for separation. The method then allows online mass spectrometry detection of separated analytes either in the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Páger et al. developed a CIEF‐MS method applying narrow range ampholytes by sequential injection . They showed that this sequential injection protocol enabled the detection of CIEF‐separated proteins.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Páger et al. developed a CIEF‐MS method applying narrow range ampholytes by sequential injection . They showed that this sequential injection protocol enabled the detection of CIEF‐separated proteins.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Such a configuration permits focusing to be executed under concomitant mobilization effected by EOF [11][12][13][14][15][16][17][18][19], application of hydrodynamic flow, electrophoretic transport when the leading electrode solution contains a counter ion other than H 3 O + and OH − [18,[20][21][22][23][24][25] or with combinations of these principles [18,23]. These approaches are reported to be attractive for hyphenation of CIEF with ESI-MS via use of volatile electrolytes such as formic acid and ammonium hydroxide [17,19,26] and for on-target fraction collection for offline coupling of CIEF and MALDI-MS [23]. In this context, Kilár et al introduced a sequential injection configuration where the carrier ampholytes and samples are injected separately [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…These approaches are reported to be attractive for hyphenation of CIEF with ESI-MS via use of volatile electrolytes such as formic acid and ammonium hydroxide [17,19,26] and for on-target fraction collection for offline coupling of CIEF and MALDI-MS [23]. In this context, Kilár et al introduced a sequential injection configuration where the carrier ampholytes and samples are injected separately [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations